Emerging Global Markets: The Voice of Arab Consumers - Vadakepat, Vanaja Menon (Indian Journal of Marketing, 2013)
Offering the most conducive business environment to global marketers, the UAE has emerged as one of the fast growing Arab markets in the Middle East. With high disposable income, the dynamic consumption behavior of UAE consumers always challenges global traders. The entrepreneurs who operate in and from UAE are, therefore, obligated to learn about consumers' changing buying behaviour. Several studies could be cited on consumer movements, but no explicit effort appears to have been made to examine Arab consumers' attitude towards global marketing, and their intelligence to judge the necessity of consumerism. The present descriptive study, focusing on the Abu Dhabi market, examined the views of the respondents on a range of market strategies that excited the voice of Arab consumers. The objective of the present study is to explore the level of awareness on consumerism in the dawn of global markets in Abu Dhabi. The survey was administrated in two zones in the Emirate, with a sample comprising of hundred Arab consumers. The survey found Arab consumers welcoming global markets. However, they demanded government initiatives to assure quality of products, pricing, distribution and prevention of misleading promotions. The study is vindicated by the UAE government's initiative to expand the functioning of consumer courts across the Emirates.